2011
DOI: 10.1089/scd.2010.0180
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Neural-Crest-Derived Intermediate Pluripotent Progenitors into Committed Periodontal Populations Involves Unique Molecular Signature Changes, Cohort Shifts, and Epigenetic Modifications

Abstract: Intermediate progenitor populations play a crucial role in the regional specification and differentiation of the cranial neural crest. On the basis of global gene expression profiles, gene cohort expression levels, and epigenetic modifications, we have defined key factors involved in the differentiation of dental follicle (DF) intermediate progenitors into periodontal lineages, including alveolar bone (AB) osteoblasts, cementoblasts, and periodontal ligament (PDL) cells. When comparing differentially expressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 57 publications
0
52
0
3
Order By: Relevance
“…However, the protein expression was not observed by immunocytochemistry staining. In addition, it has been identified that periodontal ligament tissues contained a subpopulation that is derived from neural crest cells [10,25,26]. Thus, these cells may contain the intrinsic characteristics of neuroectodermal lineage.…”
Section: Osathanon Et Almentioning
confidence: 99%
“…However, the protein expression was not observed by immunocytochemistry staining. In addition, it has been identified that periodontal ligament tissues contained a subpopulation that is derived from neural crest cells [10,25,26]. Thus, these cells may contain the intrinsic characteristics of neuroectodermal lineage.…”
Section: Osathanon Et Almentioning
confidence: 99%
“…ASPN and anti-proliferative IGFBP5 (insulin-like growth factor binding protein) were up-regulated by transcription factor TonEBP (tonicity-responsive enhancer binding protein) in mouse embryonic fibroblasts and may be involved in renal adaptation to hypertonic stress 40 . Co-regulation of ASPN and IGFBP5 was also observed in alveolar bone osteoblasts 33 . Schaeffer et al 42 focused on gene expression in the murine prostate rudiment at three time points during the first 48 h of exposure to androgen, which initiates proliferation and invasion of prostate epithelial buds into surrounding urogenital sinus mesenchyme.…”
Section: Asporin Expression and Its Regulation In Normal Tissues And mentioning
confidence: 84%
“…Another study showed that expression of ASPN, TGF-β1, and TGF-β3 (transforming factor beta) in osteoblasts from subchondral bone and in particular osteophytes of osteoarthritic patients was higher than that of non-osteoarthritic patients 32 . High ASPN expression was also found in alveolar bone osteoblasts 33 . The family of small leucine rich repeat proteoglycans is commonly found in cartilage tissues where ASPN competes with other SLRPs in many processes 34 .…”
Section: Asporin Expression and Its Regulation In Normal Tissues And mentioning
confidence: 93%
See 1 more Smart Citation
“…Neural crests are multipotent cells with a high regenerative capacity (Rinon et al 2011). They play a vital role in tooth development by inducing the growth of the mesenchymal component, including odontoblasts, dental pulp, apical vessels and periodontal ligaments (Dangaria et al 2011). SHEDs have the same molecular properties as neural crests and stem cells.…”
Section: Stem Cells Of Human Exfoliated Deciduous Teeth (Sheds)mentioning
confidence: 99%